Motivation of Volunteers during Great Patriotic War (Case Study of Rostov Region) - O. A. Eldinov (Научный диалог)
This article explores the motivations behind citizens joining volunteer formations during the Great Patriotic War. The study relies on archival and published sources on the history of volunteer movements in the Rostov region. The research is based on a military-anthropological approach, aiming to understand the worldview of volunteers and the qualitative and quantitative parameters of volunteer movements in the Don region. The relevance of the study lies in the necessity of attracting more attention from researchers to understand what drove individuals to act during wartime. A detailed analysis of the archives at the Center for Documentation of Recent History of Rostov Region revealed characteristic models of voluntarism. The author concludes that the mechanism of agitation and propaganda intertwines with deeply personal motives of resistance against the enemy. A classification of tools influencing participants’ motives is proposed, including visual imagery, state symbolism, the work of agitators and propagandists, and oath-taking. The novelty of the research lies in the author’s exploration of the mechanism influencing public consciousness in a specific region with limited time to prepare the population for resistance against the adversary.